Efektivitas Terapi Musik terhadap Penurunan Tingkat Nyeri pada Pasien Pasca Operasi: Scooping Review (Lembaga Pengembangan Kinerja Dosen, 2026)
Postoperative pain is a common physiological response following surgical procedures, and its suboptimal management can have physiological and psychological effects, including sleep disturbances, decreased functional capacity, increased anxiety, and deterioration in quality of life. This scoping review aims to describe the empirical evidence regarding the effectiveness of music therapy in reducing the intensity of postoperative pain in surgical patients. A systematic search was conducted through four major databases (ScienceDirect, PubMed, Neliti, and Google Scholar) using Boolean operators and keywords such as ‘postoperative pain,’ ‘music therapy,’ and ‘pain scale.’ Inclusion criteria included articles published in the last decade, in English or Indonesian, and available in full text format. In accordance with PRISMA-ScR guidelines, this review analysed 10 articles. The synthesis of results showed that music therapy consistently reduced pain intensity, anxiety, and analgesic requirements through mechanisms such as increased endorphin secretion, decreased stress hormone levels, and activation of the gate control theory. Typically administered for 15–30 minutes, music therapy is a safe, cost-effective, and patient-acceptable non-pharmacological modality. This intervention is recommended as an adjunct component in perioperative pain management in nursing practice, although further standardised research is needed to improve consistency.